Unmet Needs of Women Living with Parkinson's Disease: Gaps and Controversies. Issue 3 (20th January 2022) - Subramanian, Indu; Mathur, Soania; Oosterbaan, Annelien; Flanagan, Richelle; Keener, Adrienne M.; Moro, Elena
Abstract: Personalized medicine considering sex, gender, and cultural context has become the vanguard of delivery of care. However, women's issues in Parkinson disease (PD), especially from a psychosocial standpoint, have been an overlooked field. The key research areas include women‐inclusive drug and device studies and genetic and hormonal considerations. Moreover, women with PD need to be educated and empowered on how to communicate their symptoms and needs, get engaged in research, get organized as a community, and support one another. Women with PD need tools to help track and convey their unique motor and nonmotor symptoms and psychological and social support needs. The management of PD needs to be customized to include the unique stages of women's lives, including menstrual cycles, pregnancy, perimenopause, menopause, and postmenopause. Specific guidelines for the use of hormonal treatments and customized dopamine replacement dosing need to be developed. Women need guidance on culturally sensitive wellness and self‐care strategies that are customized for them. Basic core competencies in knowledge for all clinicians treating women with PD need to be established, including how to accurately diagnose, proactively identify, and treat the symptoms of PD in women and to ensure timely referral for specialty care, advanced therapies, and research studies. Caregivers and families need guidance on holistically supporting women with PD. The voices of women living with PD must be amplified to catalyze real change in this neglected field. This paper provides an overview of the current knowledge, gaps, and possible strategies to deal with the unmet needs of women living with PD with a focus on the clinical and psychosocial aspects. © 2022 International Parkinson and Movement Disorder Society